Legal Protection for Retail Investors in Green Sukuk: An Analysis of Sharia Economic Law - Ramadhan, Muhammad Nurfaidh; Mutiara Hapiz; Syarah, Vhamvhilla Rulvi; Hardiansyah, Dika; Ramadhani, Ananda (Universitas Islam Negeri Raden Intan Lampung, 2025)
The development of Indonesia’s Green Sukuk has grown significantly, particularly in attracting retail investors to sustainable and Sharia-compliant financing instruments. However, this growth has not been matched by comprehensive analysis of investor protection. This study examines the legal protection for retail investors in Green Sukuk by integrating perspectives from Islamic economic law, OJK regulations, and international green financing standards. Using a normative legal method through statute, conceptual, and comparative approaches and supported by limited interviews with OJK representatives, the study finds that Indonesia’s regulatory framework provides a solid legal foundation but lacks mandatory green standards, leaving room for potential greenwashing. Current investor protection focuses more on financial stability and product legality rather than transparency of green projects and verification of environmental impact. The study concludes that stronger green regulation, improved transparency, and harmonization with international standards are needed. Further research is recommended on investor behavior and the effectiveness of green disclosure mechanisms.